Effect of basalt fibres reinforcement and aluminum trihydrate on the thermal properties of intumescent fire retardant coatings - Yasir, M. (Institute of Physics Publishing, 2017)
This research is carried out in order to study the synergistic effect of aluminium trihydrate and basalt fibres on the properties of fire resistant intumescent coatings. Intumescent fire retardant coatings were developed using different flame retardants such as ammonium polyphosphate, expandable graphite, melamine and boric acid. These flame retardants were bound together with the help of epoxy binder along with curing agent. Furthermore, individual and combinations of aluminium trihydrate and basalt fibres was incorporated in the formulations to analyse mechanical and chemical properties of the coatings. Char expansion was observed using furnace test, thermogravimetric analysis was used to determine residual weight, X-Ray Diffraction was performed to investigate compounds present in the char, shear test was conducted to determine char strength and scanning electron microscopy analysis was performed to observe morphology of the burnt char. From the microscopic investigation it was concluded that the dense structure of the char increased the char integrity by adding basalt and aluminium trihydrate as fillers. X-Ray Diffraction results shows the presence boron phosphate, and boric acid which enhanced the thermal performance of the coating up to 800°C. From the Thermogravimetric analysis it was concluded that the residual weight of the char was increased up to 34.9 for IC-B2A4 which enhanced thermal performance of intumescent coating. © Published under licence by IOP Publishing Ltd.